Adherence to quality criteria improves concordance between transient elastography and ElastPQ for liver stiffness assessment—A multicenter retrospective study. Issue 10 (October 2018) - Ferraioli, Giovanna; De Silvestri, Annalisa; Reiberger, Thomas; Taylor-Robinson, Simon D.; de Knegt, Robert J.; Maiocchi, Laura; Mare, Ruxandra; Bucsics, Theresa; Atzori, Sebastiana; Tinelli, Carmine; Sporea, Ioan
Abstract: Background: Assessment of liver stiffness provides important diagnostic and prognostic information in patients with chronic liver disease. Aims: To investigate whether the use of quality criteria (i) improves the concordance between transient elastography (TE) and a novel point shear wave elastography technique (ElastPQ ® ) and (ii) impacts on the performance of ElastPQ ® for liver fibrosis staging using TE as the reference standard. Methods: In this multicenter retrospective study, data of patients undergoing liver stiffness measurements (LSM) in five European centers were collected. TE was performed with FibroScan ® (Echosens, France) and ElastPQ ® with EPIQ ® or Affiniti ® systems (Philips, The Netherlands). The agreement between TE and ElastPQ ® LSMs was assessed with Lin's concordance correlation coefficient (CCC). Diagnostic performance of ElastPQ ® was assessed by the area under receiver operating characteristic (AUROC) curves. Results: Overall, 664 patients were included: mean age: 54.8(13.5) years, main etiologies: viral hepatitis (83.1%) and NAFLD (7.5%). CCC increased significantly when LSMs with ElastPQ ® were obtained with IQR/M ≤ 30% (p < 0.001). The diagnostic performance of ElastPQ ® for fibrosis staging also increased if LSM values were obtained with IQR/M ≤ 30%. Conclusion: Quality criteria should be followed when using ElastPQ ® for LSM, since the concordance with TE fibrosis staging was better at an ElastPQ ® IQR/M ≤ 30.